Role of NUCB2/Nesfatin-1 in the Hypothalamic Control of Energy Homeostasis - Stengel, A.; Taché, Y. (Hormone and Metabolic Research, 2013)
Hunger and satiety are regulated in a complex fashion by a few food intake stimulatory (orexigenic) and a multitude of inhibitory (anorexigenic) factors produced in the periphery (mainly in the gastrointestinal tract) or directly in the brain. Within the brain, the hypothalamus plays a pivotal role as a production site of food intake regulatory factors. Importantly, this site integrates peripheral and central signaling factors to orchestrate food intake and in the long term body weight. Our knowledge on these regulatory pathways is not static but rather rapidly changing as new factors as well as up- and downstream signaling pathways of already known transmitters are uncovered. Hypothalamic nucleobindin2 (NUCB2), the precursor of nesfatin-1, was first described in 2006 and nesfatin-1 found to be a novel anorexigenic modulator of food intake and body weight. The initial report stimulated several groups to investigate the biological actions of nesfatin-1 and subsequent studies delineated the underlying brain mechanisms involved in its food reducing effect. Of interest was the demonstration that NUCB2 also exerts its anorexigenic action in the paraventricular nucleus of the hypothalamus and is regulated at this site by changes in metabolic status with a diurnal rhythm inversely related to that of feeding in rats. The present review describes the current state-of-knowledge on central nesfatin-1’s effects on food intake and body weight and highlights important missing links regarding cellular signaling mechanisms involved in nesfatin-1’s action.
Keywords: body weight; food intake; hypothalamus; NUCB2; nesfatin-1; obesity; satiation